Study on the CM EMI Generation Characteristics of the Si/SiC Hybrid Switch at Different Switching Patterns and Gate Resistors - Zhu, Yong; Peng, Zishun; Dai, Yuxing; Zhao, Zhenxing; Liu, Zeng; Zheng, Zijie (Frontiers in Electronics, 2022)
The switching patterns and gate resistor of the Si/SiC hybrid switch are the key to realizing its own highly efficient and reliable operation. However, as an important performance indicator, the common mode (CM) electromagnetic interference (EMI) noise caused by the Si/SiC hybrid switch lacks comprehensive research, which means that it is not clear how the switching patterns and gate resistor affect CM EMI. In this paper, the Si/SiC hybrid switch-based boost converter is established at first. Then, by analyzing the spectral characteristics of the CM voltage of the Si/SiC hybrid switch, the CM EMI generation characteristics of the Si/SiC hybrid switch at different switching patterns and gate resistors are revealed. Furthermore, the analysis and experimental results can be used to comprehensively guide the design of the gate drive pattern, gate resistor, and EMI suppression strategy.